Die Reform des Arbeitnehmerüberlassungsgesetzes und Tarifautonomie - Tobias Brändle; René Kalweit; Marcel Reiner (Hochschule Pforzheim, 2024)
– A major goal of the reform of the German Temporary Employment Act (Arbeitnehmerüberlassungsgesetz, AÜG) on April 1, 2017, was to strengthen collective bargaining autonomy. This paper uses quantitative and qualitative methods to show whether and to what extent this goal has been achieved and how we can empirically assess why the goal has (not) been achieved. The reform of the AÜG enabled the bargaining partners to adopt collective bargaining exemptions, which was also done in large parts of the bargaining landscape. It can be seen that the reform of the AÜG had an impact on the collective bargaining coverage of temporary employment agencies. In contrast, neither the collective bargaining coverage of temporary agency workers nor of deployment firms has been significantly influenced by the reform of the AÜG. It becomes clear that this is due in particular to loopholes in the law as well as to the general complexity of collective bargaining regulations.
Keywords: J42; J51; J63; 330; temporary agency employment; employee leasing; temporary staffing; collective bargaining